Pengkanunan Hukum Islam di Indonesia (Kajian dalam Bidang Hukum Keluarga) - Karimatul Ummah (Fakultas Hukum Universitas Islam Indonesia, 2003)
The effort of positioning the Islamic Law is very urgent to put into in action in order that the law material is applicable at the Constitution Court in which finally it becomes absolute competence of Religion Court. Besides that, it is aimed to unify the law toward the certainlaw, because the judges at the Religion Court would refer to the same law.